Study of Genetic Diversity of Native Indonesian Catfish Based on Nucleotide Sequences of the ND1 Gene - Rini Widayanti; Siti Qiorotun Naimah; Rahma Prihutami; Trini Susmiati (Jurnal Sain Veteriner, 2022)
One of the native catfish to Indonesia is the baung fish (Hemibagrus). Baung fish are found in rivers in Sumatra, Kalimantan and Java. The catfish population is declining, thus conservation is needed to prevent extinction. To conduct an effective conservation efforts, molecular studies are needed to confirm the fish species from the three islands. Mitochondrial DNA is one of the markers that is often used to see the lineage and kinship of animals for conservation purposes. The purpose of this study is to determine the genetic diversity of the NADH Dehydrogenase Subunit I (ND1) gene catfish from each of these locations, can be used as a genetic marker. Samples were obtained from their natural habitat, namely Magelang (5), Palembang (3), Riau (2), Samarinda (2), 2 from Sintang, and 3 from Banjarmasin. The DNA of the fish sample was then isolated and then used as a template for amplification of DNA fragments using PCR techniques. Amplikon (PCR product) was then purified by gel extraction and then sequenced to determine the DNA sequence. The potential of DNA sequences as catfish genetic markers was proven by analyzing genetic diversity between species using the MEGA version 7.0 program (Kumar et al., 2016). The sequencing results 972 nucleotides composing the ND gene, and found differences in 268 nucleotide sites and 47 amino acid sites. Based on the nucleotide sequence of the ND1 gene, catfish from the Progo river (Magelang, Central Java), the Musi river (Palembang, Sumatra), the Kampar river (Riau), the Kapuas river (Sintang, Kalimantan), the Martapura river (Banjarmasin), the Mahakam river (Kalimantan) is included in the Hemibagrus sp.; catfish from the Elo river (Magelang, Central Java) belongs to the genus Mystus sp.; catfish from the Bengawan Solo river (Bojonegoro, East Java) belongs to the Pangasius sp.